2005
DOI: 10.1038/sj.leu.2403756
|View full text |Cite
|
Sign up to set email alerts
|

Gender aspects in chronic myeloid leukemia: long-term results from randomized studies

Abstract: Gender-related aspects in chronic myeloid leukemia (CML) have not been studied well. We therefore analyzed 856 patients with Ph/BCR-ABL-positive CML from the German randomized CML-studies I (interferon a (IFN) vs hydroxyurea (HU) vs busulfan) and II (IFN þ HU vs HU alone). The median observation time was 8.6 years. A total of 503 patients (59%) were male. Female patients were older (51 vs 46 years; Po0.0001), presented with lower hemoglobin (11.7 vs 12.5 g/dl; Po0.0001), higher platelet counts (459 vs 355 Â 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
31
1
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 70 publications
(45 citation statements)
references
References 29 publications
11
31
1
2
Order By: Relevance
“…21 Whether increased androgenic sex hormone levels in young males do account for the preponderance of multiple myeloma in very young male adults, however, remains speculative as yet. Overall survival, however, did not differ between male and female patients, which is in contrast to several other cancers such as chronic myeloid leukemia, 22 acute myeloid leukemia, 23 and others that show significantly longer survival in female patients.…”
Section: Discussionmentioning
confidence: 49%
“…21 Whether increased androgenic sex hormone levels in young males do account for the preponderance of multiple myeloma in very young male adults, however, remains speculative as yet. Overall survival, however, did not differ between male and female patients, which is in contrast to several other cancers such as chronic myeloid leukemia, 22 acute myeloid leukemia, 23 and others that show significantly longer survival in female patients.…”
Section: Discussionmentioning
confidence: 49%
“…59 Despite presenting with a less favorable risk profile, female patients have been shown to respond better to therapy than males and resulted with a significantly better overall survival in earlier trials and at least comparable outcomes in more recent studies. 59,60 In contrast, there is emerging evidence at least in a t(8;21)-positive subgroup of pediatric patients with acute myeloid leukemia (AML), that male gender is a positive prognostic factor for survival. 61 Other studies have not shown any gender difference concerning outcome in adult AML patients.…”
Section: Myeloid Leukemiamentioning
confidence: 87%
“…For example, recent studies suggest that women may be more susceptible to tobacco-induced lung cancer (26). There have also been reported gender differences in the development of chronic myeloid leukemia (27), colon cancer (28), multiple sclerosis (29), and diabetic cardiomyopathy (30). A report of the Surveillance, Epidemiology and End Results program of the National Cancer Institute revealed the cancer incidence for all sites to be greater in males compared with females, and the cancer mortality rate is similarly higher in males (31).…”
Section: Introductionmentioning
confidence: 99%